Large-scale investigation on healthy status of teachers in Jiangsu Province, China - Zheng, Chunlin; Shi, Cheng; Bai, Jianling; Shao, Wentao; Zhang, Chunlan; Bu, Jin (Progress in Nutrition, 2019)
Objective: We conducted this cross section study to investigate the basic health status of teachers in Jiangsu. Design: Healthy data of teachers from Chinese Teacher Cohort were collected by an online questionnaire and scored by a diet behavior system with maximum score of 28. Setting: The health of teachers is not only a sociopolitical topic, but also an interdisciplinary challenge, while few researches focused on the basic healthy information of above teacher population. Subjects: A total of 22,956 teachers aged 20-65 year registering in Jiangsu Province Education System completed the questionnaire survey. Results: The average Dietary habits score of participants was 14.0±3.0 based on a full score of 28, which is the worst. The Dietary habits score increased with age (P<0.001). A worse score was detected in males compared with females, in the subjects with abnormal BMI (<18.5 or >25) compared with the ones with normal BMI (18.5-23.0) (P<0.001), in the subjects with smoking or drinking history compared the ones without such history (both P<0.001), and in the subjects from South of Jiangsu (vs Central region, P<0.05; vs North region, P<0.01). A higher score (21-28 scores vs. 7-13 scores) was significantly negatively associated with high blood pressure, high serum glucose, hyperlipidemia, and sleeplessness (all P were <0.001), after adjusted for sex, age, smoking and drinking status. Conclusion: The results indicate baseline healthy data of teachers in Jiangsu, and provide reliable evidences for future feasible strategies making on prevention of occupation related chronic diseases including high blood pressure, high serum glucose, hyperlipidemia, and sleeplessness. Knowledge of healthy habits and nutritional knowledge in the teacher population needs significant improvement. Developing age/gender-specific program for promoting healthy lifestyle among teachers is recommended.